China's International Poverty Reduction Center as a Platform for South-South Learning - Wu, Zhong; Karp, Philip; Wang, Yan (2012)
After attending a South-South experience-sharing event in China, a number of African officials wondered: "How come China is able to develop and retain its implementation capacity, whereas our countries suffer from brain-drain?"